The 10-year follow-up data of the Euro-Lupus Nephritis Trial comparing low-dose and high-dose intravenous cyclophosphamide. Issue 01 (20th January 2009) - Houssiau, F A; Vasconcelos, C; D'Cruz, D; Sebastiani, G D; de Ramon Garrido, E; Danieli, M G; Abramovicz, D; Blockmans, D; Cauli, A; Direskeneli, H; Galeazzi, M; Gül, A; et al.
Abstract : Objective: To update the follow-up of the Euro-Lupus Nephritis Trial (ELNT), a randomised prospective trial comparing low-dose (LD) and high-dose (HD) intravenous (IV) cyclophosphamide (CY) followed by azathioprine (AZA) as treatment for proliferative lupus nephritis. Patients and methods: Data for survival and kidney function were prospectively collected during a 10-year period for the 90 patients randomised in the ELNT, except in 6 lost to follow-up. Results: Death, sustained doubling of serum creatinine and end-stage renal disease rates did not differ between the LD and HD group (5/44 (11%) vs 2/46 (4%), 6/44 (14%) vs 5/46 (11%) and 2/44 (5%) vs 4/46 (9%), respectively) nor did mean serum creatinine, 24 h proteinuria and damage score at last follow-up. Most patients in both groups were still treated with glucocorticoids, other immunosuppressant agents and blood pressure lowering drugs. After 10 years of follow-up, the positive predictive value for a good outcome of an early drop in proteinuria in response to initial immunosuppressive therapy was confirmed. Conclusion: The data confirm that a LD IVCY regimen followed by AZA—the "Euro-Lupus regimen"—achieves good clinical results in the very long term.